Differentiated instruction in the mathematics classroom: Teachers’ teaching experience in a teacher professional development - Fina Hanifa Hidayati (Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Differentiated instruction is an approach that can be used to facilitate students with various characteristics and help them to master mathematics in every topic learned. This study describes teachers’ performance in implementing differentiated instruction. In the second secondary school level, thirty mathematics teachers designed mathematics lessons using differentiated instruction in different topics, peer-reviewed, and peer-presented. Implementing the lesson in a real classroom was done while conducting classroom observation to see what works well during the learning process and improve it. Qualitative descriptive method was used to describe the process of research and analyze findings during the lesson through observation and forum group interview. From this process, teachers prepared instruction based on students’ abilities, took into account personal mathematics understanding, and helped students achieve mathematics learning goals. Teachers also learned strategies for helping students learned. Meanwhile, students enjoyed the learning process through their different ways of learning.